Bereaved Parent Perspectives on End-of-Life Conversations in Pediatric Oncology - Rhonda Robert; Shehla Razvi; Lisa L. Triche; Eduardo Bruera; Karen M. Moody (MDPI AG, 2022)
Background: Professional education pertaining to end-of-life care with pediatric oncology patients is limited. Pediatric trainees learn about end-of-life conversations largely from the provider's perspective. Bereaved parents can inform the education of oncologists and the interdisciplinary team by sharing their perceptions and preferences through personal narratives. Methods: The aim of this project was to enhance the healthcare teams' understanding of bereaved parents' end-of-life care preferences through narratives. Bereaved parents were recruited from our institution's Pediatric Supportive Care Committee membership. Parents were tasked with identifying elements of care that were of the greatest importance to them, based upon their personal experiences during their child's end-of-life care. Narratives were analyzed using standard qualitative methods. Results: Parents of five patients participated, including four mothers and three fathers. Ten themes summarizing essential elements of end-of-life care were identified, including early ongoing and stepwise prognostic disclosure, honoring the child's voice, support of hope and realism, anticipatory guidance on dying, and continued contact with the bereaved. Conclusion: Bereaved parents emphasize the need for providers to have ongoing honest conversations that support realism and hope that can help them to best prepare for their child's end of life and to remain in contact with them after death.